Highly Efficient Nonfullerene Polymer Solar Cells Enabled by a Copper(I) Coordination Strategy Employing a 1, 3, 4‐Oxadiazole‐Containing Wide‐Bandgap Copolymer Donor. Issue 28 (21st May 2018) - Xu, Xiaopeng; Li, Zuojia; Bi, Zhaozhao; Yu, Ting; Ma, Wei; Feng, Kui; Li, Ying; Peng, Qiang
Abstract: A novel wide‐bandgap copolymer of PBDT‐ODZ based on benzo[1, 2‐b:4, 5‐b′ ]dithiophene (BDT) and 1, 3, 4‐oxadiazole (ODZ) blocks is developed for efficient nonfullerene polymer solar cells (NF‐PSCs). PBDT‐ODZ exhibits a wide bandgap of 2.12 eV and a low‐lying highest occupied molecular orbital (HOMO) level of −5.68 eV, which could match well with the low‐bandgap acceptor of 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone)‐5, 5, 11, 11‐tetrakis(4‐hexylthienyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]‐dithiophene (ITIC‐Th), inducing a good complementary absorption from 300 to 800 nm and a minimal HOMO level offset (0.1 eV). The PBDT‐ODZ:ITIC‐Th devices exhibit a large open‐circuit voltage ( V oc ) of 1.08 eV and a low energy loss ( E loss ) of 0.50 eV, delivering a high power conversion efficiency (PCE) of 10.12%. By adding a small amount of copper(I) iodide (CuI) as an additive to form coordination complexes in the active blends, much higher device performances are achieved due to the improved absorption and crystallinity. After incorporating 4% of CuI, the PCE is elevated to 12.34%, with a V oc of 1.06 V, a J sc of 17.1 mA cm −2 and a fill factor of 68.1%. This work not only provides a novel oxadiazole‐containing wide‐bandgap polymeric donor candidate for high‐performance NF‐PSCs but also presents an efficient morphology‐optimization approach to elevate the PCE of NF‐PSCs for future practical applications. Abstract : A novel 1, 3, 4‐oxadiazole‐based wide‐bandgap copolymer of PBDT‐ODZ is developed for efficient nonfullerene organic solar cells. This copolymer exhibits a large bandgap and a deep highest occupied molecular orbital (HOMO) level, which could match well with the low‐bandgap ITIC‐Th acceptor. Enabled by a copper(I) coordination strategy, high power conversion efficiency of 12.34% is achieved when employing copper(I) iodide as the solvent additive.